The Role of Managerial Ability in Increasing Firm Value Through Environmental Performance - Rustan, Alexandra Ellysa; Asri, Marselinus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
This study aims to investigate the effect of managerial ability on firm value through environmental performance. The theories used in this study to support the explanation of the relationship between variables are agency theory, stakeholder theory, and RBV theory. This study uses secondary data in the form of annual financial reports. The population of this study were all non-financial companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The number of companies that meet the criteria of this study are 45 companies with a total sample of 225 data units. This research data analysis technique uses path analysis. The results of this study indicate that managerial ability has a negative and significant effect on environmental performance, managerial ability has a positive and significant effect on firm value, and environmental performance cannot mediate the effect of managerial ability on firm value.